Endovascular Treatment of Large Vessel Occlusion Strokes Due to Intracranial Atherosclerotic Disease - Jin Soo Lee; Seong-Joon Lee; Ji Man Hong; Francisco José Arruda Mont Alverne; Fabricio Oliveira Lima; Raul G. Nogueira (Journal of Stroke, 2022)
Mechanical thrombectomy (MT) has become the gold-standard for patients with acute large vessel occlusion strokes (LVOS). MT is highly effective in the treatment of embolic occlusions; however, underlying intracranial atherosclerotic disease (ICAD) represents a therapeutic challenge, often requiring pharmacological and/or mechanical rescue treatment. Glycoprotein IIb/IIIa inhibitors have been suggested as the best initial approach, if reperfusion can be achieved after thrombectomy, with angioplasty and/or stenting being reserved for the more refractory cases. In this review, we focus on the therapeutic considerations surrounding the endovascular treatment of ICAD-related acute LVOS.